Kabinet Merah Putih dan Representasi Perempuan di Eksekutif: Pelengkap di Meja Kekuasaan Tanpa Landasan Hukum yang Mengikat - Khalifa Nur Khaliq Pohan; Andzi Salwa Salsabila; Anggrelita Mutiara Salsabila Dewi; Aniqotul Ummah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
Women's representation in the executive power structure in Indonesia, especially in the 2024 Red and White Cabinet, shows the strong dominance of a patriarchal political system that does not provide equal space for women. Although Indonesia has implemented an affirmative policy in parliament in the form of a 30% quota for women, a similar policy has not been implemented at the executive level. As a result, the appointment of women in the cabinet is highly dependent on the political will of the president and is symbolic. This research uses a qualitative approach with a case study method, which analyzes how the lack of legal regulations has a direct impact on the quantity and quality of women's representation. The findings show that women are often placed in non-strategic ministries, experience tokenism, and do not have strong legitimacy to influence policy. The absence of a legal umbrella makes women's representation volatile, unsustainable, and vulnerable to political change. In the context of gender justice, these conditions reflect structural inequalities that need to be addressed through institutional reform and affirmative legislation. This research recommends the need for strict and binding regulations to ensure that women are not merely present as a complement to power, but as actors who have a strategic and empowered position in the public decision-making process